Rest Period Healing Effect on Viscoelastic Continuum Damage Behaviour of Asphalt Mixture: Experimental Quantification and Numerical Verification of a New Approach - Su, Yang (Curtin University, 2019)
Rest period healing effect on viscoelastic continuum damage behaviour of asphalt mixture is systematically through simplified VECD and 4PB beam fatigue tests with various length of rest period after each load cycle. A new equation is proposed to interpret damage characteristic curves with rest period. Novel methods are developed to model beam fatigue tests results through derived VECD healing model. The new functions are evaluated and verified by comparison of simulation and experiment results.